Concentrations, distribution, and risk assessment of heavy metals in the iron tailings of Yeshan National Mine Park in Nanjing, China. (May 2021) - Young, G.; Chen, Yanqing; Yang, Mei
Abstract: For the first time, a field survey was conducted to investigate the present situation, vertical distribution and ecological risks of heavy metals (Cu, Zn, Mn, Cr, Pb and As) from 21 in-situ samples drilled out from Yeshan iron mine tailings in the Jiangsu Province of China. The heavy metal contents obtained for the tailing wastes in decreasing order were as follows: Mn > Cu > Zn > As > Cr > Pb. The contents of heavy metals varied with depth, and the variation trends were not completely consistent. Vertical distribution profiles showed that heavy metals accumulated in certain strata. Both the monomial potential ecological risk factor ( E ) and the risk quotient ( RQ ) showed a high ecological risk for Cu, Mn and As. The comprehensive ecological risk index ( RI ) also indicated that the wastes presented a high ecological risk level, to which Cu, Mn and As were the key contributors. Our study showed that the health of individuals, especially children, living in the mining-impacted areas could be affected by the potential noncarcinogenic risk of copper, manganese and the carcinogenic risk of arsenic. Graphical abstract: Image 1